Steeping of biofortified orange maize genotypes for ogi production modifies pasting properties and carotenoid stability - Ortiz, Darwin; Nkhata, Smith; Rocheford, Torbert R.; Ferruzzi, Mario G. (MDPI, 2019)
Biofortified orange maize open-pollinated varieties and hybrids with higher provitamin A carotenoids (pVACs) have been released in sub-Saharan Africa and will be introduced throughout the local food systems. This study assessed the impact of steeping, a traditional processing method, on retention of carotenoids and starch pasting properties of porridges made from select biofortified maize genotypes. Steeping had a modest effect (<9% loss) on total carotenoid stability during relatively shorter steeping periods (<72 h). However, more extended steeping periods (up to 120 h) had a detrimental effect on total carotenoid recovery (61% loss). Xanthophylls showed greater stability (82% retention) compared to carotenes (30% retention) during subsequent wet cooking of fermented flours. Interestingly, steeping of maize did modify pasting properties, with peak viscosities increasing from 24–72 h of steeping potentially impacting cooking stability. These results suggest that steeping can impact carotenoid retention and potentially optimal steeping times would be 24–72 h for acceptable carotenoid retention.